MEDICAL AND ENVIRONMENTAL APPLICATIONS OF ACTIVATED CHARCOAL: REVIEW ARTICLE - Alkhatib, Ahed J; Al Zailaey, Khalid (European Scientific Journal, ESJ, 2015)
This review article purposes to focus on the roles associated with activated charcoal (AC). While AC is mainly associated with treatment of poisoning substances, it has other important roles in the treatment of patients with chronic kidney disease which enhances the outcome of renal dialysis. We also indicated to the use of AC in providing protection for workers against vapors in working atmosphere through the use of charcoal cartridge. AC has potential roles in removal of heavy metals from environment particularly water. AC has therapeutic and environmental applications due to its large surface area. Taken together, AC various applications which have to taken seriously to offer benefits other than being used for treating poisoning substances.